The role of root development of Avena fatua in conferring soil strength. Issue 7 (1st July 2015) - Dumlao, Matthew R.; Ramananarivo, Sophie; Goyal, Vivek; DeJong, Jason T.; Waller, Jack; Silk, Wendy K.
Abstract : Premise of the study: Roots play an important role in strengthening and stabilizing soils. Existing models predict that tensile strength and root abundance are primary factors that strengthen soil. This study quantified how both factors are affected by root developmental stage. Methods: Focusing on early development of Avena fatua, a common grassland species with a fibrous root system, we chose three developmental stages associated with major changes in the root system. Seeds were planted in rhizotrons for easy viewing and pots to allow root growth surrounded by soil. Tensile strength was determined by subjecting root segments to a progressively larger pulling force until breaking occurred. Root abundance at two depths was characterized by the cross‐sectional area of the roots divided by the area of the soil core (i.e., root area ratio). Shear strength of 50 mm saturated soil columns was determined with a modified interface direct shear device. Key results: Tensile strength increased by a factor of ≥15× with distance from the root tip. Thus, soil‐strengthening properties increased with root cell development. Plants grown under dry soil conditions produced roots with higher maximal tensile strength (41.9 MPa vs. approximately 17 MPa), largely explained by 33% thinner diameters. Over 7 weeks of root growth, root abundance increased by a factor of 4.8× while saturated soil shear strength increased by 24% in the upper soil layer. Conclusions: Root development should be incorporated into models of soil stability to improve understanding of this important environmental property.